2018
DOI: 10.15671/hjbc.2018.266
|View full text |Cite
|
Sign up to set email alerts
|

A Reassessment of the Conservation Status of Endangered Aphanius sureyanus (Neu, 1937) (Cyprinodontiformes:Aphaniidae) and the First Data on its Reproduction in Captivity

Abstract: A phanius sureyanus (Burdur Dişlisazancığı) Türkiye'nin güneydoğusunda yer alan Burdur Gölü'ne endemiktir. Bu çalışmada, eldeki veriler ve son gözlemlere dayanarak türün güncel koruma durumu kısaca değerlendirilip sunulmuştur. Aphanius sureyanus IUCN tarafından yayınlanan Tehlike Altındaki Türlerin Kırmızı Listesi'nde "Tehlike Altında" (EN) kategorisinde değerlendirilmektedir. Tür üzerindeki başlıca tehditlerin Burdur Gölü'nün kuruması ve tuzluluğun ve kirliliğin artması olduğu öne sürülmektedir. Elde edilen b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…We collected information on fish species and their distribution and population status in the BCB from a wide range of literature [47][48][49][50][51][52][53][54][55][56]. The validity of the fish names was checked using FishBase [57] and the Catalog of Fishes [58].…”
Section: Fishmentioning
confidence: 99%
See 3 more Smart Citations
“…We collected information on fish species and their distribution and population status in the BCB from a wide range of literature [47][48][49][50][51][52][53][54][55][56]. The validity of the fish names was checked using FishBase [57] and the Catalog of Fishes [58].…”
Section: Fishmentioning
confidence: 99%
“…The Anatolia region is a hotspot for the diversity of the killifish family (Aphaniidae), a euryhaline group that tolerates changes in salinity and can live in both fresh and brackish waters [65,66]. Many species of the Anatolichthys genus have a limited distribution in the BCB, with some species restricted to only a few springs or lakes, such as Anatolichthys transgrediens, which is only found in Lake Acıgöl during the spring [48], Anatolichthys saldae, which is only found in Lake Salda, and Anatolichthys sureyanus, which only occurs in Lake Burdur [51]. The endangered A. sureyanus has been highlighted as being under threat due to massive water abstraction and damming [48,63].…”
Section: Fishmentioning
confidence: 99%
See 2 more Smart Citations
“…In Anatolia, where the genus is remarkably diverse, there are 18 endemic species, 8 of which are represented by small isolated populations that are known from a single lake or spring and the remaining species are known from a single (or rarely two) watershed area (Freyhof et al, 2017; Yo gurtçuo glu and Freyhof, 2018). Although only four of the Anatolian species are listed as threatened, it has been suggested that most of the species among those not yet assessed are endangered as a result of their highly localised occurrence and ongoing threats in their habitats (Yo gurtçuo glu, 2018).…”
mentioning
confidence: 99%